Developing a procedural model to determine the null curriculum - Cahapay, Michael B.; Fajardo, Amelia C.; Muega, Maricris B. Acedo; Calingasan, Lorina Y.; Javiniar, Joel C.; Salubayba, Teodora M. (Quezon City College of Education, University of the Philippines Diliman, 2022)
What is not taught nor learned, or the null curriculum, is a significant part of the school curriculum, and how it can be determined is essential. This study aimed to develop a procedural model to determine the null curriculum. Set in the context of the Philippines elementary teacher education program, it collected data through document reviews, structured interviews, participant observations, metadata activities, and questionnaire surveys, involving participants with experience in curriculum development. The gathered data were subjected to thematic analysis and descriptive statistics. The results initially indicated that a procedure entails four components: goal, prerequisites, instructions, and challenges. Guided by these components, the procedure to determine the null curriculum was consequentially designed with a terminal goal broken down into two enabling goals, knowledge support and material resources, direct instructions to act and the invitations to explore, and limitations and caveats. The overall strength of the procedure mainly rested on its clear guidelines, processed materials, and logical design. It extracted the not or less emphasized intellectual processes and absent contents that constitute the null curriculum. Towards the end of the study, a model that follows a systems approach, with its three keys elements of inputs, process, and output incorporating the features of the final procedure, was developed. This model presents scholars, practitioners, and researchers with a structure to determine the null curriculum. In the light of the results, future researchers are recommended to test the applicability of the model in other contexts to further broaden the procedural knowledge on the null curriculum. Specific recommendations for theory and practice are likewise given.
Thesis
Includes bibliographic references (209-228 leaves)
Keywords: Education, Elementary -- Curricula -- Philippines; Curriculum planning -- Philippines; Elementary school teachers -- Education -- Philippines; Elementary school teachers -- Training of -- Philippines